Future Socio-Political Scenarios for Aquatic Resources in Europe: A Common Framework Based on Shared-Socioeconomic-Pathways (SSPs) - Pinnegar, John K.; Hamon, Katell G.; Kreiss, Cornelia M.; Tabeau, Andrzej; Rybicki, Sandra; Papathanasopoulou, Eleni; Engelhard, Georg H.; Eddy, Tyler D.; Peck, Myron A. (Frontiers in Marine Science, 2021)
It has proven extremely challenging for researchers to predict with confidence how human societies might develop in the future, yet managers and industries need to make projections in order to test the robustness (or otherwise) of adaptation and mitigation strategies and therefore to build resilience to long-term shocks. An alternative approach has been to map out plausible scenarios that can cut through the thousands of permutations of climate vs economic vs social vs political possibilities. In the present paper, we describe efforts to design exploratory scenarios with a particular focus on European aquaculture and fisheries. Four socio-political-economic futures were developed, based partly on the IPCC SRES (Special Report on Emissions Scenarios) framework and partly on the newer system of Shared Socio-economic Pathways (SSPs). ‘Off the shelf’ narrative material as well as quantitative outputs were ‘borrowed’ from these earlier frameworks but supplemented with material generated through in-depth stakeholder workshops involving industry and policy makers. Workshop participants were tasked to outline how they thought their sector might look under the four future worlds and, in particular, to make use of the PESTEL conceptual framework (Political, Economic, Social, Technological, Environmental and Legal) as an aide memoire to help define the scope of each scenario. This work was carried out under the auspices of the EU Horizon 2020 project CERES (Climate change and European aquatic RESources), and for each ‘CERES scenario’ (World Markets, National Enterprise, Global Sustainability and Local Stewardship), additional quantitative outputs were generated, including projections of future fuel and fish prices, using the MAGNET (Modular Applied GeNeral Equilibrium Tool) modelling framework. In developing and applying the CERES scenarios, we have demonstrated that the basic architecture is sufficiently flexible for use at a wide diversity of scales. We argue that it would be beneficial if a similar scenarios framework, based around SSPs, could be adopted more broadly, in order to facilitate global cross-comparison of fisheries and aquaculture model outputs and to harmonize communication regarding bioeconomic impacts of climate change into the future.